2020
DOI: 10.22270/jddt.v10i4-s.4312
|View full text |Cite
|
Sign up to set email alerts
|

TIRYAQ E ARBA: A classical Unani Formulation to boost immunity

Abstract: Unani System of medicine is one among the oldest systems of medicine that prevails till date with its efficient drugs derived from animal, plant and mineral resources. Over 2400 years ago the father of medicine, Hippocrates practiced it, however His medicine included a great deal of ancient Egyptian Medicine as well as important components of the ancient Mesopotamian traditions. This system of medicine has a detailed description of drugs that are utilized in many infectious diseases like influenza, pneumonia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One of the important preparations called Tiryaq‐e‐Arba consists of Gentiana lutea L., Aristolochia longa L, Commiphora myrrha (Nees) Engl, and Laurus nobilis L. This preparation is mainly used as an immune booster to fight epidemics (A. A. Khan, Bashir, & Akhtar, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the important preparations called Tiryaq‐e‐Arba consists of Gentiana lutea L., Aristolochia longa L, Commiphora myrrha (Nees) Engl, and Laurus nobilis L. This preparation is mainly used as an immune booster to fight epidemics (A. A. Khan, Bashir, & Akhtar, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unani add-on regimen includes a semisolid Unani pharmacopeial preparation-'Tiryaq-e-Arba', an Unani antidote for epidemics which comprises equal proportions of four herbs prepared as per the Unani Formulary, along with 'Unani Joshanda', a decoction made with three herbs. In order to obtain decoction, all three ingredients of 'Unani Joshanda', were boiled in 250 ml of water and reduced to one-half (125ml), followed by filtration [4,8,11,15,19,20]. Both the herbal Unani drug preparation were supplied by the Indian Medicines Pharmaceutical Corporation Limited (IMPCL) which is engaged in the Manufacturing and Marketing of Ayurvedic and Unani Medicines and is under the administrative control of the Ministry of AYUSH, Govternment of India.…”
Section: Study Interventionsmentioning
confidence: 99%
“…All the individual ingredients of the combination exhibit anti-viral activity in addition to anti-inflammatory, antioxidant, and immunomodulatory properties [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Recently, it was also reported that it exhibits antiviral activity against SARS-CoV-2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…IIkhani et al (2019), Baig et al (2018) studied relationship between Temperament and diabetes [33][34]. In the current epoch, the importance of Temperament in dealing with COVID 19 were studied by Nikhat and Fazil (2020), Khan et al (2020) [35][36].…”
Section: -2-unani Temperament (Mizaj)mentioning
confidence: 99%